Preface (Journal of physics. Conference series, 2023)
It is a matter of great pleasure for the organizers to bring out the Conference proceedings of the 6th National Conference on Advanced Materials and Radiation Physics (AMRP-2023) in Journal of Physics: Conference Series. The 6th National Conference on Advanced Materials and Radiation Physics (AMRP-2023) was held during May 18-19, 2023 through HYBRID Mode at Sant Longowal Institute of Engineering and Technology, Longowal, Punjab (INDIA). The AMRP-2023 conference is an important event that brings academics and researchers from all over India to share their professional experiences, expand their professional knowledge and receive updates on the latest advances in the field of advanced materials and radiation Physics.Materials science is an interdisciplinary field which deals with the discovery and design of new materials involving the study of materials through the materials paradigm (synthesis, structure, properties and performance). The subject covers a broad spectrum of materials science research including functional materials, synthesis and processing, theoretical analyses, characterization and properties of materials. Emphasis is also placed on the interdisciplinary nature of materials science and issues at the forefront of the field, such as energy and environmental issues, as well as medical and bioengineering applications are also discussed.The Radiation Physics is highly multidisciplinary in nature and is now the backbone of the nuclear medical diagnostics. The radiation physics research covers many areas of radiation imaging techniques, fundamental studies of semiconductor radiation detectors, detector materials, radiation interaction with matter and medical physics which aims to improve knowledge and methods in the field of radiation physics and radiation dosimetry, in order to develop new radiation measurement instruments and methods for applications in research, industry and medicine.In this conference more than 150 researchers from reputed universities/institutes have shown interest in hybrid mode participation. The conference included one key note address, four plenary talks, six invited talks, and presentation of more than 130 contributed papers via online & offline mode on different aspects of the conference theme. We extend our sincere gratitude to all the authors who submitted their papers to the AMRP conference. We also like to express our great appreciation to the Keynote, plenary and invited speakers.We are thankful to Institute administration for extending all support and motivation to organize this conference. On behalf of the Conference Organizing Committee, we would like to thank the referees for their efficient and thoughtful actions. We are grateful to the members of the Organising Committee for their efforts in making and shaping the program for AMRP 2023. Particularly, we acknowledge the publishing support from the members of Journal of Physics: Conference Series. We hope that the future AMRP will be as successful and stimulating, as indicated with the contributions presented in this volume.Organising Committee AMRP-2023List of Organising Committee is available in this Pdf.